Molecular characterization of Campylobacter isolated from chickens and humans in Northern Thailand - Meeyam T. (2014)
A study was conducted in northern Thailand to characterize Campylobacter spp isolated from chickens at farms, slaughterhouse, and chicken meat at fresh markets, and stools from chicken farmers as well as neighboring crop farmers who served as controls. The Campylobacter isolates were collected during the rainy months of the years 2000, 2001, and 2002. Standard methods were used for primary isolation and identification of Camplobacter and the resulting isolates were frozen and stored in 30% glycerol with Mueller-Hinton broth at -70°C until used in 2003. A multiplex PCR assay was used for differentiation of the Campylobacter spp. A total of 415 Campylobacter spp were isolated from 849 (48.9%) samples from chickens at the farm, slaughter house and fresh chicken meat market. Campylobacter spp were isolated from 5 of the 129 (3.9%) chicken farmers but none from the 100 neighboring crop farmers. C. jejuni was the most prevalent (42.5%) at the farm, followed by C. coli (39.1%) and other species (8.0%). In contrast, C. coli was the most prevalent at the slaughter house (72.4%) while C. jejuni was only 17.2% and others 3.4%. Similarly, at the fresh chicken market, C. coli was the most prevalent (54.4%) while C. jejuni was 26.5% and others were 13.2%. Campylobacter spp isolated from the chicken farmers were predominantly (75%) C. coli and the rest (25%) were C. jejuni. The results of the study show that both C. coli and C. jejuni are highly prevalent in chickens, along the chicken production system and in chicken farmers in northern Thailand. Critical control points for exposure and contamination of the chicken meat supply should be identified so that methods can be developed to protect human exposure to Campylobacter spp.